2017
DOI: 10.1080/17524032.2017.1400455
|View full text |Cite
|
Sign up to set email alerts
|

Corporations, Consumerism and Culpability: Sustainability in the British Press

Abstract: Sustainability and sustainable development are prominent themes in international policymaking, corporate PR, news-media and academic scholarship. Definitions remain contested, however sustainability is associated with a three-pillar focus on economic development, environmental conservation and social justice, most recently espoused in the adoption of the UN Sustainable Development Goals in 2015. In spite of its common usage, there is little research about how sustainability is represented and refracted in publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…In contrast to the meaning of sustainability defined in Western countries with dominant neoliberal environmentalism and consumerism that concentrate on individual responsibility, justice and scepticism primarily in relation to the environment (as we have discussed elsewhere Diprose et al, ), based on our discourse analysis, the Chinese government‐led interpretation of sustainability is constructed with the following two characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the meaning of sustainability defined in Western countries with dominant neoliberal environmentalism and consumerism that concentrate on individual responsibility, justice and scepticism primarily in relation to the environment (as we have discussed elsewhere Diprose et al, ), based on our discourse analysis, the Chinese government‐led interpretation of sustainability is constructed with the following two characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…As Morse (2013) indicated, the term "sustainability" is explained as more commercially biased in right-of-center reports and more socially oriented in left-of-center newspapers in Britain. Similarly, in other studies in Western contexts the concepts behind "sustainability" in media are multiple, reflecting various major political views and the different political attitudes of newspaper readers (Diprose et al, 2017;Fischer et al, 2017). Rather than the multiple meanings of sustainability interpreted in the West, the official discourse of "sustainability" represented in People's Daily is defined and explained unilaterally by the central government led by the CCP.…”
Section: " Ecological Civilization" (Shengtai Wenming): a Chinese Imentioning
confidence: 99%
“…(2) Where solutions are mentioned, they tend to be reported "with a negative bias" (Bonfadelli, 2009, p. 275) by presenting the most optimal ones as ultimately impossible to implement due to their high economic costs. (3) News articles tend to rely on a narrow range of sources from government and mainstream business (Bonfadelli, 2009;Diprose et al, 2017;Lewis, 2000;, which is not dissimilar to reporting on climate change and the environment (Anderson, 2017;Hansen, 2010) as well as general news reporting trends (Hall et al, 1978). The reliance on sources from government and mainstream business in sustainability reporting has prompted critiques that the media reinforce the preferred meanings or sustainability frames of powerful groups and institutions (Donohue, Tichenor, & Olien, 1995).…”
Section: Sustainability Coveragementioning
confidence: 99%
“…The latter promoted the idea that better environmental outcomes can be achieved through more efficient, smarter technologies. Analyzing British print newspapers, Diprose et al (2017) identified an economic frame which invoked the responsibility of businesses to work sustainably and of consumers to choose green products and it also demonstrated faith in scientific innovations. In a study of print newspapers published in the United States (US), Lewis (2000) described an economic growth frame, which presented economic development and technology as the most effective ways to achieve sustainability.…”
Section: Sustainability Coveragementioning
confidence: 99%
See 1 more Smart Citation